Shift of microbial community in gas-phase biofilters with different inocula, inlet loads and nitrogen sources. (April 2020) - Lu, Lichao; Wang, Guangchun; Yeung, Marvin; Xi, Jinying; Hu, Hong-Ying
Graphical abstract: Highlights: Genus Rhodococcus, Pseudomonas dominated in the three biofilters. Alcanivorax, Pimelobacter prefer low inlet load; higher for Zoogloea, Alkaliphilus . Pseudomonas prefer nitrate; Bacillus and Gordonia prefer ammonia. Abstract: The research on gaseous VOCs biofilters has often concentrated on process optimization. However, the microbial community change upon operating conditions is not well understood. In this study, three lab-scale biofilters treating gaseous toluene were operated for 66 days with different inocula under changes in inlet loads and nitrogen sources. Three biofilters were inoculated with activated sludge, river sediment or microbial consortia, respectively. The microbial community differed a lot initially but gradually deviated toward similar structures with the same dominant microorganisms, i.e. Proteobacteria, Actinobacteria (phylum level) and Rhodococcus, Pseudomonas (genus level). Among three biofilters, the two biofilters inoculated with activated sludge and river sediment showed higher microbial diversity, better VOCs removal performance and higher metabolic activity. Higher relative abundance of Alcanivorax (3% compared with lower than 0.03%), Pimelobacte (0.05% compared with lower than 0.01%)were detected under low inlet load, and Zoogloea (0.1%), Alkaliphilus (0.2%) were detected when the inlet load was increased. the abundance of Pseudomonas decreased from 14% to 2% when ammonia was used as n itrogen source instead of nitrate, meanwhile the abundance of Bacillus and Gordonia increased from 0.01% to 0.05% and 0.8% to 5.8% respectively. Some special organisms were observed i.e. the intestinal microorganism.